Surgical angiogenesis: a new approach to maintain osseous viability in xenotransplantation - Chung, Yang-Guk; Bishop, Allen T.; Giessler, Goetz A.; Suzuki, Osami; Platt, Jeffrey L.; Pelzer, Michael; Friedrich, Patricia F.; Kremer, Thomas (Xenotransplantation, 2010)
BACKGROUND: Large segmental osseous defects are challenging clinical problems. Current reconstructive methods, using non-viable allografts, vascularized autografts or prostheses have significant rates of serious complications and failure. These include infection, stress fracture and non-union (frozen structural allogenic bone); loosening and implant failure (prosthetic replacement); limited availability, poor match of size and shape and donor site morbidity (vascularized autograft bone). In the future, microvascular transplantation of living allogenic or xenogenic bone could solve some of these issues, combining the advantages of living bone autografts (capability of primary osseous healing, remodeling, and fracture resistance) with the ability to match size and shape, provide immediate stability and avoid donor site morbidity. Xenotransplants would be particularly attractive, as they could be readily available, if long-term bone survival could be achieved without unacceptable morbidity. Here, we present a preliminary study to evaluate a new and unique method to maintain xenogenic bone circulation without need for long-term immune modulation that depends upon generation of a neo-angiogenic circulation within the transplanted bone from recipient-derived vessels. Thus, only short-term immunosuppression would be required to achieve bone survival. - METHODS: One hundred and forty-one hamster femora were microsurgically transplanted to rats, restoring nutrient vessel circulation with standard microvascular anastomoses. At the same time, a host-derived arteriovenous bundle (AVB) was placed within the medullary canal. Two independent variables were evaluated: use of tacrolimus/cyclophosmamid immunosuppression (IS) and patency of the implanted AVB. Rats were therefore randomized to four groups; group 1-no IS + patent AVB; group 2-no IS + ligated AVB; group 3-IS + patent AVB; group 4-IS + ligated AVB. Rats were sacrificed after 1 or 2 weeks. We evaluated bone blood flow (microsphere entrapment), neoangiogenesis (microangiography and quantification of capillary density), bone necrosis rate (osteocyte counts) and nutrient pedicle rejection (microsurgical anastomotic patency). Statistical Analysis was performed with two-way ANOVA with Bonferroni adjustment. Differences were considered significant when P < 0.05. - RESULTS: Capillary density was significantly increased with a patent intramedullary AVB (groups 1/3) compared to groups with ligated AVBs (groups 3/4). Capillary sprouting was predominantly restricted to the endosteal layer. Most nutrient pedicles (78.7%) stayed patent in groups with IS (groups 3 and 4). Consequently, bone blood flow was significantly higher in groups 3 and 4 compared to groups 1 and 2. Similarly, a patent AV bundle improved flow in group 1 when compared to group 2. The bone necrosis rate was not influenced by the presence of patent AVBs but was significantly reduced in groups 3 and 4. - CONCLUSIONS: Surgical angiogenesis occurs when patent arteriovenous bundles are placed in the medullary canal of xenogenic bone and leads to increased bone blood flow. Bone viability was not significantly influenced by neoangiogenesis. Although capillary sprouting was restricted to the endosteal layer in this short term study, more complete cortical revascularization might be observed in a long-term study. Such a study should further evaluate whether these new vessels supply sufficient blood flow to maintain long-term bone viability and allow remodeling.